Extreme temperatures and household energy consumption in China: insights from adaptive behavior - Liu, Qiaohui; Yao, Tingting; Tong, Haozhi; Peng, Jiachao (Frontiers in Sustainable Cities, 2025)
The increasing frequency of extreme temperatures poses significant threats to human habitats. Utilizing data from the China Family Panel Studies (CFPS) and the Chinese Residential Energy Consumption Survey (CRECS), this study examines the effects of extreme temperatures on household energy consumption in China from an adaptive behavior perspective. The results show that each additional day of extreme high temperatures increases household energy consumption by 3.437 yuan, while each additional day of extreme low temperatures raises it by 8.071 yuan. Moreover, extreme temperatures have notably stronger impact on the energy consumption of rural, low-income, and southern households, especially with regard to extreme cold. Extreme temperatures increase energy consumption primarily by altering residents’ adaptive behaviors: they compel households to reduce spending on food and medical care, shorten work hours, and increase the use of home thermostats devices. Specifically, for each day of extreme cold, household expenditures on food and medical care decrease by 23.217 and 21.212 yuan, respectively, residents’ work hours are reduced by 0.156 h, and households add 0.079 heating devices. This conclusion not only helps to scientifically evaluate the economic cost of extreme climate, but also provides important decision-making basis for households to enhances their resilience to energy-related risks and governments to optimize energy policies.